Myofascial Trigger Points Therapy Modifies Thermal Map of Gluteal Region. (20th February 2020) - Onik, Grzegorz; Kasprzyk, Teresa; Knapik, Katarzyna; Wieczorek, Karolina; Sieroń, Dominik; Sieroń, Aleksander; Cholewka, Armand; Sieroń, Karolina
Abstract : Background . Thermal imaging may be effectively used in musculoskeletal system diagnostics and therapy evaluation; thus, it may be successfully applied in myofascial trigger points assessment. Objective . Investigation of thermal pattern changes after myofascial trigger points progressive compression therapy in healthy males and females. Methods . The study included 30 healthy people (15 females and 15 males) with age range 19–34 years (mean age: 23.1 ± 4.21). Thermograms of myofascial trigger points were taken pre- and posttherapy and consecutively in the 15 th and 30 th minutes. Pain reproducible by palpation intensity was assessed with numeric rating scale. Results . Progressive compression therapy leads to myofascial trigger points temperature (p = 0.02 ) and surface (p = 0.01 ) in males. In females no statistically significant changes were observed. Manual treatment leads to a decrease in intensity of pain reproducible by palpation in males (p = 0.03 ) and females (p = 0.048 ). Conclusions . The study indicates that myofascial trigger points reaction to applied therapy spreads in time and space and depends on participants' sex.